Re-Assessment of the Oral Salt Loading Test Using a New Chemiluminescent Enzyme Immunoassay Based on a Two-Step Sandwich Method to Measure 24-Hour Urine Aldosterone Excretion - Ozeki, Yoshinori; Kinoshita, Mizuki; Miyamoto, Shotaro; Yoshida, Yuichi; Okamoto, Mitsuhiro; Gotoh, Koro; Masaki, Takayuki; Kambara, Kengo; Shibata, Hirotaka (Frontiers in Endocrinology, 2022)
Since April 2021, the plasma aldosterone concentration has been measured by chemiluminescent enzyme immunoassay (CLEIA) in Japan. In the present study, we developed a new CLEIA using a two-step sandwich method to measure the 24-hour urine aldosterone level. We collected 115 urine samples and measured 24-hour urine aldosterone levels employing radioimmunoassay (RIA), CLEIA, and liquid chromatography–tandem mass spectrometry (LC-MS/MS). The results showed that the 24-hour urine aldosterone levels measured using CLEIA and LC-MS/MS were significantly correlated (ρ = 0.992, P < 0.0001). Based on the results of Passing–Bablok regression analysis, the slope was 0.992 and the intercept –19.3. The 24-hour urine aldosterone levels measured using CLEIA and RIA were also significantly correlated (ρ = 0.905, P < 0.0001). However, the aldosterone level measured by CLEIA was lower than that measured by RIA (slope, 0.729; intercept, 120.9). In Japan, a new guideline for primary aldosteronism has been announced, with changes in the aldosterone measurement method. The cutoff values for oral sodium loading test (OSLT) were changed, but clinical verification using real-world urine samples has not been performed. Therefore, we examined the cut-off value of the 24-hour urine aldosterone level after the OSLT. Receiver operating characteristic analysis revealed a cut-off value for primary aldosteronism of 3 μg/day.